Daya Beli Kaitannya dengan Keputusan Pembelian Smartphone Pada Agung Cellular Ciawi Di Masa Pandemi Covid-19 - Hendi Sobari; Jajang Saeful Zaman; Wita Rahmatunnisa (JURNAL EKONOMI PERJUANGAN, 2022)
During the pandemic, the need for smartphones increased due to the soaring demand for everything digital from business activities to learning activities, but on the other hand, smartphone sales declined due to this pandemic. Based on this, smartphone businesses must pay attention to the purchasing power of consumers. The purpose of this study was to determine the influence of purchasing power on smartphone purchasing decisions at Agung Cellular Ciawi during the Covid-19 pandemic. The method used in this research is descriptive quantitative. The results show that purchasing power has a significant effect on smartphone purchasing decisions at Agung Cellular Ciawi, which is 21%, and the remaining 79% is influenced by other variables apart from the purchasing power. Based on the results of the study, it is known that apart from indicators of income, price and taste, indicators of consumer optimism are found as a driving force for consumers to buy products. The conclusion from the research is that consumers decide to make a purchase by paying attention to indicators of income, price, taste and optimism. Keywords: Purchasing Power, Purchase Decision, Consumer